Low-energy impact of human cartilage: predictors for microcracking the network of collagen. Issue 4 (April 2017) - Kaleem, B.; Maier, F.; Drissi, H.; Pierce, D.M.
Summary: Objective: We aimed to determine the minimum mechanical impact to cause microstructural damage in the network of collagen (microcracking) within human cartilage and hypothesized that energies below 0.1 J or 1 mJ/mm 3 would suffice. Design: We completed 108 low-energy impact tests (0.05, 0.07, or 0.09 J; 0.75 or 1.0 m/s 2 ) using healthy cartilage specimens from six male donors (30.2 ± 8.8 yrs old). Before and after impact we acquired, imaging the second harmonic generation (SHG), ten images from each specimen (50  μ m depth, 5  μ m step size), resulting in 2160 images. We quantified both the presence and morphology of microcracks. We then correlated test parameters (predictors) impact energy/energy dissipation density, nominal stress/stress rate, and strain/strain rate to microcracking and tested for significance. Where predictors significantly correlated with microstructural outcomes we fitted binary logistic regression plots with 95% confidence intervals (CIs). Results: No specimens presented visible damage following impact. We found that impact energy/energy dissipation density and nominal stress/stress rate were significant ( P  < 0.05) predictors of microcracking while both strain and strain rate were not. In our test configuration, an impact energy density of 2.93 mJ/mm 3, an energy dissipation density of 1.68 mJ/mm 3, a nominal stress of 4.18 MPa, and a nominal stress rate of 689 MPa/s all corresponded to a 50% probability of microcracking in the network of collagen. Conclusions: An impact energy density of 1.0 mJ/mm 3 corresponded to a ∼20% probability of microcracking. Such changes may initiate a degenerative cascade leading to post-traumatic osteoarthritis.